2007
DOI: 10.1111/j.1467-8691.2007.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Employee Well‐Being and Innovativeness: An Opportunity for a Mutual Benefit

Abstract: By drawing on the Job Demands and Resources Model, this review article develops a conceptual framework to advance theoretical understanding of the relationship between job‐related demands and resources, employee well‐being and innovativeness. In conditions characterized by too high levels of demands, employees may suffer from burnout. When job resources are high, they are likely to feel engaged with their work. Burnout in turn can be seen as an inhibitor of innovativeness, and work engagement as an antecedent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 45 publications
(81 reference statements)
4
137
0
2
Order By: Relevance
“…Human resource management and organizational psychology scholars (Deery, 2002;Guest, 2002) have paid increased attention to employee's well-being and burnout (Huhtala & Parzefall, 2007). Huhtala and Parzefall (2007) investigated the relationships between employee work engagement and innovativeness of individual employees, and they found that that employee work engagement, that is, employee satisfaction and loyalty is an antecedent to innovativeness (Demerouti, Bakker, Nachreiner, & Schaufeli, 2001), and also knowledge management performance (Chou, Hsu, Yeh, & Ho, 2005).…”
Section: Relational Outcomes Of Satisfied and Loyal Employeesmentioning
confidence: 99%
“…Human resource management and organizational psychology scholars (Deery, 2002;Guest, 2002) have paid increased attention to employee's well-being and burnout (Huhtala & Parzefall, 2007). Huhtala and Parzefall (2007) investigated the relationships between employee work engagement and innovativeness of individual employees, and they found that that employee work engagement, that is, employee satisfaction and loyalty is an antecedent to innovativeness (Demerouti, Bakker, Nachreiner, & Schaufeli, 2001), and also knowledge management performance (Chou, Hsu, Yeh, & Ho, 2005).…”
Section: Relational Outcomes Of Satisfied and Loyal Employeesmentioning
confidence: 99%
“…From the employee's perspective, suggesting new ideas always comes along with certain inconveniences and exposure which might discourage employees from engaging in such kind of high-intensity behavior [17,19,64]. The theoretical model by Huhtala and Parzefall [108] suggests that employee well-being and innovativeness may constitute self-enhancing cycles. While high well-being is perceived to boost innovativeness and vice versa, low well-being may lead to a decrease in innovativeness.…”
Section: Implications For Green Employees and Green Human Resource Mamentioning
confidence: 99%
“…For example, burnout (Huhtala & Parzefall, 2007) and emotional exhaustion (Cropanzano, Rupp, & Byrne, 2003) have been negatively associated with employee innovative behaviour. Low job satisfaction and burnout are endemic in nursing (Aiken et al, 2001, Chang, Ma, Chiu, Lin, & Lee, 2009).…”
Section: Psychological Wellbeingmentioning
confidence: 99%